1991
DOI: 10.1128/iai.59.9.3323-3326.1991
|View full text |Cite
|
Sign up to set email alerts
|

Blood proteins do not promote adherence of coagulase-negative staphylococci to biomaterials

Abstract: We studied the effects of in vitro and in vivo coating of catheters with human blood proteins on binding of coagulase-negative staphylococci. Coating resulted in no enhancement of binding. Catheters coated in vitro bound fewer organisms than uncoated catheters. Host proteins do not enhance adherence of coagulase-negative staphylococci to biomaterials.Coagulase-negative staphylococci (CoNS) have become major nosocomial pathogens because of their capacity to colonize plastic biomaterials used in catheters and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 21 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…131 Although only a few coagulase-negative strains. The latter finding strain specific, adherence of clinical staphylococcal isolates was supported by the studies by Muller et al 117 and by to foreign surfaces was significantly increased by Fn, sug-Paulsson et al 135 Recently, Herrmann et al 140 also studied gesting the possible contribution of these proteins to the the mediating role of fibrinogen and fibrin and platelet pathogenesis of iv device infection. 132 integrin on S. aureus adhesion to surface-bound platelets.…”
Section: Bacterial Characteristicsmentioning
confidence: 85%
“…131 Although only a few coagulase-negative strains. The latter finding strain specific, adherence of clinical staphylococcal isolates was supported by the studies by Muller et al 117 and by to foreign surfaces was significantly increased by Fn, sug-Paulsson et al 135 Recently, Herrmann et al 140 also studied gesting the possible contribution of these proteins to the the mediating role of fibrinogen and fibrin and platelet pathogenesis of iv device infection. 132 integrin on S. aureus adhesion to surface-bound platelets.…”
Section: Bacterial Characteristicsmentioning
confidence: 85%
“…The second issue is the timing of the infection. It is possible that some host factors, such as fibronectin and albumin, may affect the vulnerability of graft to bacterial colonization 24,25 . It is also known that antibiotic prophylaxis should be started just before the surgical incision or insertion of the material, to be effective 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, plasma pre-conditioning of glass appears to reduce the adhesion of Staph. epidermidis RP62A compared with glass and this was also found for plasma pre-conditioned biomaterials (Muller et al 1991), NHLBI reference polyethylene (Wang et al 1993) and for albumin pre-conditioned titanium (McDowell et al 1995). This is not the case with other strains of Staph.…”
Section: Glass and Different Test Materials Under Different Conditionsmentioning
confidence: 66%
“…epidermidis than for other bacteria such as Staph. aureus (Muller et al 1991). Dunne and Burd (1992) showed that divalent cation concentration was an important determinant of the adhesion of Staph.…”
Section: Glass and Different Test Materials Under Different Conditionsmentioning
confidence: 99%